Law Under the Shadow of Power: Exploration of the Politicization of Law and Its Impact on Legal Quality and Law Enforcement in Indonesia - Rena Zulfaidah; Muhammad Torieq Abdillah (Pancasila and Law Review, 2025)
The principle of the rule of law (rechtsstaat) positions law as the primary safeguard of justice and democracy. In Indonesian constitutional practice, however, law often operates under political influence through legal politicization. This occurs when legal instruments are used to advance political interests in legislation, adjudication, and enforcement. Such practices undermine institutional independence, weaken enforcement quality, and erode public trust. This study examines the forms, mechanisms, and impacts of legal politicization on law and enforcement in post Reformasi Indonesia. It employs a normative juridical method with statutory and conceptual approaches, drawing on Critical Legal Studies (CLS) and analysis of statutes, court decisions, and relevant cases. The findings show that legal politicization in Indonesia is systemic and structural, reflected in agenda driven legislation, judicial intervention, the weakening of independent institutions, and selective enforcement. These patterns weaken the rechtsstaat and checks and balances while accelerating democratic decline through elite impunity and shrinking civic space. Legal politicization therefore poses a serious threat to constitutional democracy in Indonesia.